2009
DOI: 10.1007/s00066-009-2023-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Quality of Life in Patients Receiving Conformal Radiation Therapy for Prostate Cancer

Abstract: Definitive CRT for prostate cancer does not compromise global QoL during therapy and up to 2 years after treatment. It has a limited negative effect on role functioning, urinary symptoms and, to a lesser extent, on fatigue with restitution within 2 months to 1 year after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
1
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
(45 reference statements)
7
17
1
3
Order By: Relevance
“…Studies in colorectal and rectal cancer patients showed that psychosocial quality of life aspects improve over time [12,35]. Chronic fatigue and insomnia are two of the most prevalent problems in cancer patients generally, even years after therapy has been completed [5,8,10,17,20,23,36,37]. Among sexual problems, male sexual dysfunction emotional and social functioning, more gastrointestinal symptoms, and more defecation problems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in colorectal and rectal cancer patients showed that psychosocial quality of life aspects improve over time [12,35]. Chronic fatigue and insomnia are two of the most prevalent problems in cancer patients generally, even years after therapy has been completed [5,8,10,17,20,23,36,37]. Among sexual problems, male sexual dysfunction emotional and social functioning, more gastrointestinal symptoms, and more defecation problems.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that-independently of the used generic score-global HRQOL is mostly not significantly or relevantly affected by radiotherapy side effects also was reported by the majority of recent published prospective and/or longitudinal studies using 3D-CRT, IMRT, or brachytherapy (BT) alone or in combination with EBRT (Geinitz et al 2010;Goineau et al 2013;Huang et al 2010;Lips et al 2009;Pardo et al 2010;Roeloffzen et al 2010;Schaake et al 2013), even after dose escalation (Goineau et al 2013;Lips et al 2009;Marchand et al 2010), when comparing baseline global HRQOL scales with the changes during follow-up. Though some studies have the limitation of a short follow, there is a growing number of long-term studies.…”
Section: 1mentioning
confidence: 63%
“…In terms of EBRT, the mean impairments of disease-specific HRQOL are mostly reported to be slight or moderate. With regard to urinary symptom and bother scales, the most pronounced deterioration was consistently reported during the first months after treatment, with a recovery of specific HRQOL scales 1-2 years after treatment (Geinitz et al 2010;Gore et al 2009;Huang et al 2010). The further course beyond this time was reported inconsistently, with a second slight and gradual deterioration around 5 years after therapy observed in some studies (Pardo et al 2010).…”
Section: 2mentioning
confidence: 84%
See 1 more Smart Citation
“…Die Qualitätssicherung sollte sich nicht nur auf den technischen und organisatorischen Ablauf, sondern auch auf die unmittelbare Patientenbetreuung beziehen. In weiteren Studien sollte der direkte Einfluss verschiedener Betreuungsfaktoren auf die Lebensqualität der Patienten untersucht werden [8,18,19,28]. …”
Section: Schlussfolgerungenunclassified